Link Status Monitoring Technology for the Heterogeneous Network - Fuxiang ZHU; Chenghao HU; Yan LIU; Hui SUN; Jianzhao TIAN; Zhou LU (天地一体化信息网络)
Aiming at the heterogeneity,dynamics,high latency and limited resources of space-based network,the possibility of application of the existing terrestrial network management protocol used directly in space-based network had been analyzed,and the advantages and disadvantages of each network management protocol had been compared.Based on the above research,the problems caused by the direct use of traditional network management protocols had been further analyzed,such as the lack of end-to-end delay description in the MIB library and the complexity of network port traff c analysis,which is not conductive to the direct observation of network management systems.Finally,combined with the traditional network management protocol SNMP,a method suitable for monitoring the links of heterogeneous networks,including network topology,custom test of the delay and network traff c was proposed.The results of this paper have reference value for the design and construction of space-based network.